Integrated analyses uncover new features of atypical memory B cells and novel targets for intervention - Fuli Fan; Shubei Liu; Bin Wang; Xiaojian Song; Wei Wang (Immunobiology)
Background: Atypical memory B (AMB) is a novel subset of B lymphocytes, but its immune features and pathogenetic roles in systemic rheumatic diseases are still largely elusive. This study aimed to characterize transcriptomic features, immune phenotypes and potential signaling pathways of AMB, and also to confirm its alternations in systemic rheumatic diseases via combined transcriptome analyses. Method: B cell subsets and their transcriptomic signatures were identified via analyses of single cell RNA-sequencing (scRNA-seq) data. Functional characterization of AMB was performed with bioinformatics and CyTOF-based phenotyping. Alternation of AMB in systemic lupus erythematosus (SLE), rheumatoid arthritis (RA) and Sjögren's syndrome (SjS) was evaluated via bioinformatic approaches. Result: A total of 11 B cell subsets including AMB were identified through scRNA-seq transcriptome analyses. Both transcriptome analyses and CyTOF-based immune phenotyping confirmed that AMB had increased levels of TBX21 (T-bet), ITGAX (CD11c), CD19, CD20 and CXCR3 (P < 0.05), and it had decreased expressions of CD27, CD38, CXCR4, CXCR5 and CD62L (P < 0.05). More than 50 % of T-bet+ B cells did not express CD11c, and more than 30 % expressed CD27. AMB was characterized by activated mTORC1 signaling and increased p-P38 level (P < 0.05). AMB transcriptional signature was significantly enriched in the peripheral blood and disease tissues of patients of SLE, RA and SjS (P < 0.05), suggesting the expanded AMB cells in those patients. Conclusion: This study defines the transcriptomic signature, immune phenotypes and potential signaling pathways of AMB, and also confirms the involvement of AMB in systemic rheumatic diseases including SLE, RA and SjS via transcriptomic approaches. mTORC1 signaling and P38/MAPK signaling are promising therapeutic targets for systemic rheumatic diseases mediated by AMB.